Threatening and threatened: undetectability, risk and sexuality in the «treatment as prevention» for HIV-Aids era - Gagliolo, Agostina Aixa (2020)
This article recovers the experience of people with HIV residing in the Metropolitan Area of the Buenos Aires Province, around «treatment as prevention» the central core of the HIV-Aids contemporary government policies. It’s an ethnographic investigation with fieldwork (24 months of 2-3 weekly visits lasting 8-12 hours each) developes between 2016 and 2018. Our empirical corpus consists of 13 in-depth interviews and extensive records of everyday interaction observations. We analyze the ways in which the virus´' undetectability and untransmittability engage into everyday life with HIV. We show that while policies present the undetectable-untransmittable relation as key to ending the epidemic and simultaneously as a powerful tool to respond to the stigma surrounding HIV, these relations become more complex in the everyday lives of those affected by it, giving rise to tense and contradictory processes between perception-interpretation-signification and practices. Amongst these processes what stands out is a redirection in the risk of disease: from the probability of transmitting the virus to others, towards others as a source of transmission for new diseases.